Climate change: do we know how it will affect smallholder livestock farmers? - Thornton, Philip K.; Steeg, Jeannette van de; Notenbaert, An Maria Omer; Herrero, Mario (2013)
What is known about the likely impacts of climate change on resource-poor livestock keepers in the developing world? Relatively little, and the International Livestock Research Institute (ILRI) and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) are working to improve this knowledge. This Brief outlines how a group of scientists at ILRI reviewed some elements of the complex relationship between livestock and climate change in developing countries with a forward-looking approach. The objective was to help set research priorities: to inform the debate as to what research for development organizations such as ILRI could and should be doing in the area of climate change work that could add value to the large amounts of work already being carried out by the Global Change community on cropping systems and natural resources management. Originally designed to guide ILRI’s research on climate change, this work has had a broader impact by informing the investment strategies of several other research-for-development organizations, including donors.